2021
DOI: 10.1159/000515641
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Convective Therapies in Patients with Acute Kidney Injury: A Systematic Review with Meta-Analysis

Abstract: <b><i>Introduction:</i></b> In critically ill patients requiring intermittent renal replacement therapy (RRT), the benefits of convective versus diffusive clearance remain uncertain. We conducted a systematic review and meta-analysis to determine the safety, clinical efficacy, and clearance efficiency of hemofiltration (HF) and hemodiafiltration (HDF) compared to hemodialysis (HD) in patients with acute kidney injury (AKI) receiving intermittent RRT. <b><i>Method:</i>&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“… 31 , 32 In contrast, the possibility to perform high volumes of convective clearance using IRRT is more recent with the development of online HDF. In a recent meta-analysis comparing conventional HD to intermittent convective therapies, 15 we reported that only 3 small scale exploratory trials ever compared HD to HDF. 33 , 34 , 35 Most interestingly, pooling the results of these trials revealed a higher risk of in-hospital death with the use of HDF (Risk ratio: 2.07 CI: 1.04–4.11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 31 , 32 In contrast, the possibility to perform high volumes of convective clearance using IRRT is more recent with the development of online HDF. In a recent meta-analysis comparing conventional HD to intermittent convective therapies, 15 we reported that only 3 small scale exploratory trials ever compared HD to HDF. 33 , 34 , 35 Most interestingly, pooling the results of these trials revealed a higher risk of in-hospital death with the use of HDF (Risk ratio: 2.07 CI: 1.04–4.11).…”
Section: Discussionmentioning
confidence: 99%
“…33 , 34 , 35 Most interestingly, pooling the results of these trials revealed a higher risk of in-hospital death with the use of HDF (Risk ratio: 2.07 CI: 1.04–4.11). 15 Therefore, further investigation was urgently required to determine the safety and potential benefits of HDF in an ICU setting. In this cohort, we did not observe an increased risk of death with the use of HDF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This modality is named hemodiafiltration (HDF), requires an adapted dialysis machine, and is increasingly used in Europe and Asia for ESRD patients. However, its implementation in ICU settings remains limited, partly due to the need to maintain a water treatment system adapted to HDF [8]. As a result, when reporting intermittent RRT in the ICU, we generally consider only IHD.…”
Section: Modalities Characteristics: Ihd Pirrt/sled and Crrtmentioning
confidence: 99%